Educating in the Midst of Digital Flow: Teachers' Perspectives on Progressive Islamic Education and the Formation of a Resilient Generation - Mirawati, Mirawati; Musslifah, Anniez Rachmawati; Abbasov, Ramil; M.Suud, Fitriah (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2025)
The rapid development of digital technology has had a significant impact on various educational practices, including Islamic education, which are currently required to be more adaptive, contextual, and responsive to the demands of the digital era. This research aims to explore teachers’ perspectives on the concept and implementation of progressive Islamic education in forming a resilient generation. Progressive Islamic education, as defined in this study, is an approach that integrates Islamic values with 21st-century competencies, while emphasizing holistic development in the spiritual, intellectual, emotional, and social dimensions. This study uses a qualitative phenomenological method involving 12 teacher informants with diverse educational backgrounds. Data were collected through in-depth interviews and analyzed using thematic coding to identify patterns of meaning in teachers’ experiences and interpretations. These findings reveal that teachers view progressive Islamic education as a dynamic and open framework that encourages critical thinking, fosters a contextual understanding of Islamic teachings, and promotes the cultivation of ethical and social responsibility. Teachers also emphasize their role as facilitators who guide students in forming values, rather than simply transmitting religious doctrines. However, challenges remain in practice, including limited digital infrastructure, curriculum rigidity, and persistence of conventional pedagogical models. These results provide implications for systemic support and pedagogical innovation to strengthen the implementation of progressive Islamic education. This research contributes to the discourse on Islamic education reform, aligning spiritual values with the realities of digital transformation.